Study of the dielectric response of rare-earth modified pzt ferroelectric ceramics-an approach to the diffuse phase transition - Hessel, S. P.; Silva, A. C. [UNESP]; Guo, R.; Bhalla, A. S.; Guerra, J. D.S. (Wiley, 2018)
Ferroelectric systems have been widely studied during the last 40 years because of their excellent physical properties, which make them promissory materials for technological applications. In special, the lead zirconate titanate (PZT) system is one of the most investigated ferroelectric materials due to their excellent piezoelectric, pyroelectric and dielectric properties, which indeed can be easily controlled when modified with several chemical additives. Such substitutions provide some relevant characteristics for application in specific electro-electronic devices. The objective of the present work is to investigate the physical properties of rare-earth (RE) modified PZT ferroelectric ceramics. The characteristics of the phase transition have been studied in details as a function of the lanthanum content. In particular, compositions containing either normal or relaxor ferroelectric behavior showing diffuse phase transition (DPT) have been considered.